The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1007/s10126-008-9112-y
|View full text |Cite
|
Sign up to set email alerts
|

EST and Mitochondrial DNA Sequences Support a Distinct Pacific Form of Salmon Louse, Lepeophtheirus salmonis

Abstract: Nuclear deoxyribonucleic acid sequences from approximately 15

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 47 publications
(63 reference statements)
1
57
0
Order By: Relevance
“…Comparing results from these 2 oceans is of interest, but must be done with caution. This is in part due to the large genetic differences between lice collected from these 2 oceans (Todd et al 2004, Tjensvoll et al 2006, Yazawa et al 2008, and in part due to the differences in the numbers, types and biology of hosts between the 2 oceans, both within and outside marine farms. Just as for studies conducted in the Atlantic, the 2 studies conducted within the Pacific display contrasting results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing results from these 2 oceans is of interest, but must be done with caution. This is in part due to the large genetic differences between lice collected from these 2 oceans (Todd et al 2004, Tjensvoll et al 2006, Yazawa et al 2008, and in part due to the differences in the numbers, types and biology of hosts between the 2 oceans, both within and outside marine farms. Just as for studies conducted in the Atlantic, the 2 studies conducted within the Pacific display contrasting results.…”
Section: Discussionmentioning
confidence: 99%
“…A study based upon RAPD analysis (Dixon et al 2004) reported a highest pairwise F ST among samples from Scotland of 0.68, and the majority > 0.2. In a study of mtDNA in the Pacific (Boulding et al 2009), which might not be directly comparable due to the large genetic differences between lice in the Pacific and Atlantic (Todd et al 2004, Tjensvoll et al 2006, Yazawa et al 2008), a pairwise F ST of 0.19 was reported between L. salmonis samples taken on wild and farmed salmon co-existing in the Broughton archipelago. Studies revealing highly significant genetic variation among groups of lice collected within a small region have suggested that their observations may reflect combinations of restricted gene flow, and/or post-settlement selection mediated through local environmental factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, L. salmonis is rare on juvenile pink salmon in areas with no fish farms (9). L. salmonis occurs in the Atlantic and Pacific oceans, but the Pacific form is clinically less pathogenic than the Atlantic form (10), and the two forms have significant genetic differences (11,12). One other sea louse species, Caligus clemensi, occurs on pink salmon, but it is more common on other fish hosts (13).…”
mentioning
confidence: 99%
“…Variability of pink salmon returns has been attributed to changes in climate (Downton & Miller 1998, Morita et al 2006, genetic variability (Geiger et al 1997), coded wire tagging or fin clipping (Wertheimer et al 2002), exposure to weathered crude oil during early development (Bue et al 1996, and differences in food availability and size of alevins (Cooney & Brodeur 1998). Recent papers have correlated infestations of parasitic copepods (sea lice) with pink salmon population decline (Krkosek et al 2006(Krkosek et al , 2007; however, Pacific strains of parasitic copepods (Yazawa et al 2008) cause minimal or no mortality with environmentally relevant infestations under controlled laboratory conditions (Jones et al 2007, Webster et al 2007.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%